2006
DOI: 10.1682/jrrd.2005.07.0118
|View full text |Cite
|
Sign up to set email alerts
|

Status of the feline retina 5 years after subretinal implantation

Abstract: Abstract-Retinal prosthetics are designed to restore functional vision to patients with photoreceptor degeneration by detecting light and stimulating the retina. Since devices are surgically implanted into the eye, long-term biocompatibility and durability are critical for viable treatment of retinal disease. To extend our previous work, which demonstrated the biocompatibility of a microphotodiode array (MPA) for 10 to 27 months in the normal feline retina, we implanted normal cats with an MPA implant backed w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 26 publications
0
13
0
Order By: Relevance
“…Late stage interventions will need to circumvent the consequences of both gliosis and the remodeling that occurs in second order neurons. Early intervention will also be key for retinal prosthetic approaches (Jensen and Rizzo, 2006; Pardue et al, 2006; Besch et al, 2008; Pardue et al, 2008; Butterwick et al, 2009), in order to take advantage of the high degree of preservation of retinal circuits at the level of the inner retina which our data and others (Mazzoni et al, 2008) suggest remains largely intact in the retinas of the rd10 mouse model of RP , even following extended photoreceptor degeneration.…”
Section: Discussionmentioning
confidence: 84%
“…Late stage interventions will need to circumvent the consequences of both gliosis and the remodeling that occurs in second order neurons. Early intervention will also be key for retinal prosthetic approaches (Jensen and Rizzo, 2006; Pardue et al, 2006; Besch et al, 2008; Pardue et al, 2008; Butterwick et al, 2009), in order to take advantage of the high degree of preservation of retinal circuits at the level of the inner retina which our data and others (Mazzoni et al, 2008) suggest remains largely intact in the retinas of the rd10 mouse model of RP , even following extended photoreceptor degeneration.…”
Section: Discussionmentioning
confidence: 84%
“…There are various types of visual prostheses, and according to the locations that are stimulated, they can be generally divided into the following categories: epiretinal, 1,3,[19][20][21][22] subretinal, 2,8,13,[23][24][25] suprachoroidal, 4,15,26,27 intrapapillary, 28 extraocular, 12 thalamic, 7 cortical, 6,10,11 and optic nerve (ON). 5,14 Among them, the ON approach may potentially achieve artificial vision over a relatively large area of the visual field.…”
Section: Resultsmentioning
confidence: 99%
“…A previous study on the biocompatibility of a nondegradable subretinal prosthetic reported unintended photoreceptor degeneration. 27 Presumably, the prosthetic blocked the flow of nutrients from the choroid=RPE to the photoreceptor layer leading to the observed degeneration.…”
Section: Discussionmentioning
confidence: 99%